Cognitive–Linguistic Skills Explain Chinese Reading Comprehension Within and Beyond the Simple View of Reading in Hong Kong Kindergarteners. Issue 1 (31st August 2022) - Pan, Dora Jue; Lin, Dan
Abstract: In this study, we investigated the direct and indirect associations of different cognitive–linguistic skills and Chinese reading comprehension in Hong Kong kindergarteners. We assessed 179 children's nonverbal IQ, cognitive–linguistic skills, word reading, listening comprehension, and reading comprehension. Results showed significant correlations between all variables and reading comprehension. Further path analysis results indicated that rapid automatized naming, orthographic knowledge, and morphological awareness contributed to reading comprehension via word reading. Nonverbal IQ and vocabulary knowledge were associated with reading comprehension through listening comprehension. Beyond that, nonverbal IQ and morphological awareness still contributed directly to reading comprehension. Overall, our findings elucidated the importance of nonverbal IQ and cognitive–linguistic skills within the framework of the simple view of reading in Chinese and highlighted the unique roles of nonverbal IQ and meaning‐related skills in Chinese reading comprehension, which contributed to understanding the simple view of reading in Chinese. Abstract :